2002
DOI: 10.1063/1.1489091
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of (Zn1−yMgy)1−xAlxO ceramics prepared by the polymerized complex method

Abstract: ( Zn 1−y Mg y ) 1−x Al x O powders were synthesized by the polymerized complex method and then consolidated by spark plasma sintering apparatus. The microscopic structure and thermoelectric properties were examined comparing with the experimental results of the samples prepared by the conventional solid-state reaction method. A small amount of ZnAl2O4 spinel phase as the second phase was observed in the sintered samples with x⩾0.02 by x-ray diffraction and a scanning electron microscope. The grain size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 17 publications
6
48
1
Order By: Relevance
“…Most of these processes include melting the elemental powders of constituents, using high energy ball milling and finally having a high range of annealing step from 60 hours to almost 200 hours in some cases [8,9,[11][12][13][14][15][16]. Recently, Biswas et al and Ianniduo et al have adopted microwave synthesis for skutterudites production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these processes include melting the elemental powders of constituents, using high energy ball milling and finally having a high range of annealing step from 60 hours to almost 200 hours in some cases [8,9,[11][12][13][14][15][16]. Recently, Biswas et al and Ianniduo et al have adopted microwave synthesis for skutterudites production.…”
Section: Introductionmentioning
confidence: 99%
“…Skutterudites have an effective TE operational range from 650K to 950 K. Among the different types of skutterudites compounds, CoSb 3 based members have attracted by far the greatest interest because of constituents' abundant availability and less cost [7]. Iron substituted CoSb 3 , FexCo 1-x Sb 3 , have been reported to display good performance as a p-type TE material, in terms of its TE figure of merit (ZT), and abundance of the constituent elements [8][9][10][11][12][13][14]. The ZT can be improved via introduction of dopants, nanoengineering and in case of skutterudites, introducing rare earth elements in the crystal cages to reduce the thermal conductivity [1,[4][5][6] due to rattling of the fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the doped ZnO samples reported thus far, Al-doped ZnO exhibited the highest ZT value. [9][10][11][12][13][14][15][16][17] A relatively high thermal conductivity within the range of 20-40 WÁm À1 ÁK À1 at room temperature, generally observed in doped ZnO samples, prevents us from obtaining a considerably large ZT value. Therefore, it is very important to decrease the lattice thermal conductivity of ZnO-based materials for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…Katsuyama et al reported that the dense sintered ZnAlO systems with a fine microstructure were obtained by making use of the PC method and SPS technique. 15) As a result, the smaller grain size led to an enhancement of the phonon scattering resulting in a decrease of the thermal conductivity, especially at low temperature. In the present paper, we have examined the thermoelectric properties and microstructure of the annealed PC samples after SPS, and discussed their differences among the SSR sample, the sintered PC sample without pressure and the annealed PC sample after SPS.…”
Section: Introductionmentioning
confidence: 99%